Implementasi Kurikulum MBKM Berbasis Kearifan Lokal melalui Program Penguatan Profil Pelajar Pancasila di MTs - Rosita, Fadma; Gunawan P., M. Rudi (Mataram University, 2025)
The purpose of this study is to describe the implementation process of the Merdeka Belajar curriculum at MTs N I Lombok Timur, through the P5 Program based on local wisdom of the Sasak tribe which focuses on culture and traditional food. The study was conducted by describing the implementation of MBKM with a focus on school readiness for MBKM, the role of stakeholders in the implementation of MBKM, and the Pancasila student profile strengthening program (P5). This type of research is qualitative descriptive research, the research was conducted at MTs N I Lombok Timur, using Grade 8 Students as Subjects. Data collection techniques in this study used several techniques, namely interviews, observations and supported by documentation. This school has implemented the MBKM curriculum based on local wisdom through the P5 program in accordance with the provisions of the MBKM curriculum. Several things that support the implementation of this MBKM curriculum have also been attempted by the school through the school's readiness for the MBKM curriculum implementation process, and also maximizing the role of stakeholders very well. The P5 program has also been implemented well, and also collaborated with the community who helped teachers in running the P5 program based on local wisdom of the Sasak tribe, namely traditional food. The traditional food made is tembrodok. After being made with the right direction, this traditional cake was sold by students in the school environment. Based on the results of the description that has been presented, and seen from the readiness of the school and stakeholders who play a role according to their fields and duties, it can be concluded that the school has succeeded in implementing the MBKM curriculum according to the rules and objectives of the MBKM curriculum.